2016
DOI: 10.1002/celc.201600130
|View full text |Cite
|
Sign up to set email alerts
|

Pure Pyridinic Nitrogen‐Doped Single‐Layer Graphene Catalyzes Two‐Electron Transfer Process of Oxygen Reduction Reaction

Abstract: A post‐treatment approach is presented to prepare nitrogen‐doped single‐layer graphene via ultraviolet/ozone (UV/O3) irradiation followed by NH3 annealing. Under optimal experimental conditions, a maximum atomic ratio (N/C) of 16.6 % can be reached. X‐ray photoelectron spectroscopy analysis reveals that only one type of pyridinic N is doped in the graphene lattice, which can be used as an ideal platform to investigate its catalytic activity toward oxygen reduction reaction (ORR). Electrochemical results demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…However, the dominance of pyridinic N sites in the catalyst will cause a high density of lone‐pair electrons, and this high density of polarized pyridinic N will largely repel O 2 molecules due to their high density of lone‐pair electrons, which hinders the electron transfer between C(ς + ) and O═O. Therefore, the high portion of pyridinic N–C configuration in a carbon plane should not be the reason for the high ORR activities, which is in accordance with the literature …”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…However, the dominance of pyridinic N sites in the catalyst will cause a high density of lone‐pair electrons, and this high density of polarized pyridinic N will largely repel O 2 molecules due to their high density of lone‐pair electrons, which hinders the electron transfer between C(ς + ) and O═O. Therefore, the high portion of pyridinic N–C configuration in a carbon plane should not be the reason for the high ORR activities, which is in accordance with the literature …”
Section: Resultssupporting
confidence: 85%
“…On the other hand, the nature of the particular N species has caused considerable controversy because some research groups[55,62c] suggested a possible role of pyridinic N as an active site in ORR. However, Zheng et al recently showed that the ORR on pyridinic N‐doped graphene mainly occurs via the 2e − electron transfer process and not effectively via the 4e − process. Moreover, for ORR, the faster adsorption of O 2 molecules on the surface of the catalysts is a crucial step to obtain enhanced catalytic performance, and the logic behind the incorporation of the nitrogen in the carbon planes is to induce the polarization by generation of C(ς + ) and N(ς − ), which provides a convenient way for O 2 adsorption on catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…Also, the total nitrogen contents of in our catalyst are less than 3 at.% and comparatively lower than other N-doped carbon catalyst reported by previous studies. [29][30][31][32][33][34][35][36][37][38] The catalytic activity can be drastically improved by applying C-N precursors with higher nitrogen ratio, which should increase the total nitrogen content. Also, post-annealing under lower temperature (under 400 o C) could increase the crystallinity of amorphous carbon with limited evaporation of nitrogen content.…”
Section: Electrocatalytic Activitiesmentioning
confidence: 99%
“…30 Also, Zheng et al revealed that pure pyridinic-N doped graphene catalysed twoelectron transfer process of ORR. 31 On the other hand, Wang et al proposed that graphitic-N atoms in the carbon matrix facilitated electron transfer from the carbon electronic bands to the anti-bonding orbital of O 2 . 32 Kim et al showed that the graphitic-N provided the most pronounced ORR activity improvement, especially in terms of current density.…”
Section: Introductionmentioning
confidence: 99%
“…However, to date, this research field is still very young, and is only limited to theoretical calculations. [226][227][228] It could be very interesting to follow further pyridinic N configuration have rarely been reported, [229,230] let alone their applications in LIBs.…”
Section: Discussionmentioning
confidence: 99%